Hubungan usia dan tingkat pengetahuan calon pengantin wanita dengan persiapan kehamilan pertama - Ariani, Lidya; Miskiyah, Miskiyah; Virgian, Kharima; Nurayuda, Nurayuda (Holistik Jurnal Kesehatan, 2025)
Background: Prospective brides and grooms are a strategic target group in efforts to improve their health before pregnancy. Before the wedding, many prospective brides and grooms do not have enough knowledge and information about reproductive health in a family, so that after marriage pregnancies are often not planned well and are not supported by optimal health status. Purpose: To determine the relationship between age and knowledge level of prospective brides with first pregnancy preparation. Method: This descriptive analytical study used a cross-sectional approach and was conducted in April-May 2024. The study population was all prospective brides and grooms visiting the Tanjung Enim Community Health Center, Lawang Kidul District, Muara Enim Regency. A sample of 30 prospective brides and grooms was selected using accidental sampling. Data analysis used univariate and bivariate methods (Chi-Square correlation formula). Results: The chi-square test for age yielded a significance level of 0.012 (<0.05), thus rejecting Ho, indicating a significant relationship between the bride's age and preparation for her first pregnancy. Furthermore, the chi-square test for knowledge yielded a significance level of 0.019, indicating a significant relationship between the bride's level of knowledge and preparation for her first pregnancy. Conclusion: There is a relationship between the bride's age and her knowledge regarding preparation for her first pregnancy, with a p-value of <0.05. Suggestion: Health workers should pay more attention to ensuring that each prospective bride understands the importance of information about her first pregnancy by providing counseling materials and health tests. Keywords: Age; Level of Knowledge; Pregnancy; Prospective Bride.   Pendahuluan: Calon pengantin merupakan kelompok sasaran yang strategis dalam upaya peningkatan kesehatan masa sebelum hamil. Menjelang pernikahan, banyak calon pengantin yang tidak mempunyai cukup pengetahuan dan informasi tentang kesehatan reproduksi dalam berkeluarga, sehingga setelah menikah kehamilan sering tidak direncanakan dengan baik serta tidak di dukung oleh status kesehatan yang optimal. Tujuan: Untuk mengetahui hubungan usia dan tingkat pengetahuan calon pengantin wanita dengan persiapan kehamilan pertama. Metode: Penelitian deskriptif analitik dengan pendekatan cross sectional, dilaksanakan pada bulan April-Mei 2024. Populasi studi penelitian ini adalah semua calon pengantin wanita yang berkunjung ke Puskesmas Tanjung Enim Kecamatan Lawang Kidul Kabupaten Muara Enim. Sampel diambil menggunakan accidental sampling dengan jumlah 30 catin wanita. Analisis data menggunakan univariate dan bivariate (rumus korelasi Chi-Square). Hasil: Uji chi square usia diperoleh signifikansi sebesar 0.012 (< 0.05) maka Ho ditolak, sehingga ada hubungan bermakna antara usia calon pengantin wanita dengan persiapan kehamilan pertama. Selain itu, hasil uji chi square pengetahuan diperoleh signifikansi sebesar 0.019, sehingga ada hubungan bermakna antara tingkat pengetahuan calon pengantin wanita dengan persiapan kehamilan pertama Simpulan: Adanya hubungan antara usia dan pengetahuan calon pengantin wanita terhadap persiapan kehamilan pertama dengan p-value < 0.05. Saran: Bagi tenaga kesehatan agar lebih memperhatikan setiap calon pengantin untuk memahami pentingnya informasi tentang kehamilan pertama dengan cara memberikan materi konseling dan tes kesehatan.   Kata Kunci: Calon Pengantin Wanita; Kehamilan; Tingkat Pengetahuan; Usia.